Transcriptional Regulation of Endothelial Cell Tissue Factor Expression during Rickettsia rickettsii Infection: Involvement of the Transcription Factor NF-κB - Shi, Rui-Jin (American Society for Microbiology, 1998)
The vascular endothelial cell (EC) is a primary target of infection with Rickettsia rickettsii, the etiologic agent of Rocky Mountain spotted fever. Changes in gene transcription elicited by intracellular infection, including EC expression of the coagulation pathway initiator known as tissue factor (TF), may contribute to the vascular pathology observed during disease. Nuclear run-on analysis of uninfected and infected, cultured human endothelial cells revealed that the rate of TF mRNA transcription is enhanced more than twofold at 3 h following infection, thus coinciding with increased steady-state levels of TF mRNA. TF mRNA remained relatively unstable during infection, with a half-life of 1.6 h. The eukaryotic protein synthesis inhibitor cycloheximide did not block R. rickettsii-induced increase in TF mRNA levels and actually resulted in its superinduction, thus revealing that de novo synthesis of host cell protein was not prerequisite to this transcriptional response. Involvement of the transcription factor NF-κB in R. rickettsii-induced TF expression was demonstrated by using two unrelated inhibitors of NF-κB activation. The antioxidant pyrrolidinedithiocarbamate and the proteasome inhibitor N-tosyl-l-phenylalanine chloromethyl ketone blocked expression of TF mRNA and activity during infection. This study demonstrates that R. rickettsii infection results in transcriptional activation of the TF gene and that this response involves activation of the transcription factor NF-κB.